Comparison of Mortality Risk Models in Patients with Postcardiac Arrest Cardiogenic Shock and Percutaneous Mechanical Circulatory Support - Georgios Chatzis; Birgit Markus; Styliani Syntila; Christian Waechter; Ulrich Luesebrink; Holger Ahrens; Dimitar Divchev; Bernhard Schieffer; Konstantinos Karatolios (Journal of Interventional Cardiology)
Background. Although scoring systems are widely used to predict outcomes in postcardiac arrest cardiogenic shock (CS) after out-of-hospital cardiac arrest (OHCA) complicating acute myocardial infarction (AMI), data concerning the accuracy of these scores to predict mortality of patients treated with Impella in this setting are lacking. Thus, we aimed to evaluate as well as to compare the prognostic accuracy of acute physiology and chronic health II (APACHE II), simplified acute physiology score II (SAPS II), sepsis-related organ failure assessment (SOFA), the intra-aortic balloon pump (IABP), CardShock, the prediction of cardiogenic shock outcome for AMI patients salvaged by VA-ECMO (ENCOURAGE), and the survival after venoarterial extracorporeal membrane oxygenation (SAVE) score in patients with OHCA refractory CS due to an AMI treated with Impella 2.5 or CP. Methods. Retrospective study of 65 consecutive Impella 2.5 and 32 CP patients treated in our cardiac arrest center from September 2015 until June 2020. Results. Overall survival to discharge was 44.3%. The expected mortality according to scores was SOFA 70%, SAPS II 90%, IABP shock 55%, CardShock 80%, APACHE II 85%, ENCOURAGE 50%, and SAVE score 70% in the 2.5 group; SOFA 70%, SAPS II 85%, IABP shock 55%, CardShock 80%, APACHE II 85%, ENCOURAGE 75%, and SAVE score 70% in the CP group. The ENCOURAGE score was the most effective predictive model of mortality outcome presenting a moderate area under the curve (AUC) of 0.79, followed by the CardShock, APACHE II, IABP, and SAPS score. These derived an AUC between 0.71 and 0.78. The SOFA and the SAVE scores failed to predict the outcome in this particular setting of refractory CS after OHCA due to an AMI. Conclusion. The available intensive care and newly developed CS scores offered only a moderate prognostic accuracy for outcomes in OHCA patients with refractory CS due to an AMI treated with Impella. A new score is needed in order to guide the therapy in these patients.